Brand Reputation and the Cost of Capital: Evidence of Adopting a Brand Name as the Corporate Name - YiLin Wu (The Journal of Entrepreneurial Finance (JEF), 2011)
This paper studies how the capital market perceives brand name adoption. I distinguish between brand adoption and radical type of corporate name change. A brand adoption name change occurs when the firm adopts one of its well-established brands as its new corporate name and a radical type occurs when the new name is semantically unrelated to firm history. Improved profitability and increased net investment accompany brand name adoption. After controlling for changes in the competing information sources, the accompanying improved economic performance, and the endogeneity of the decision to adopt a brand name, I find that, while there are no intertemporal variations in the cost of capital for a radical name change, a brand name adoption is associated with a lower cost of capital following the name change, suggesting that brand reputation is a valuable asset.
Keywords: G32; M13; 650; Cost of Capital; Brand; Discount for Lack of Brand